Impact of Capital Expenditure and Public Utility Customers to Economic Development of District-City in Sumatra-Indonesia - Susetyo, Didik; Zunaidah, Zunaidah; Rohima, Siti; Valeriani, Devi; Bashir, Abdul (International Journal of Economics and Financial Issues, 2018)
The research problem is how to influence local public utility capital expenditures, the amount of household electric customers, the number of clean water customers, the number of telephone customers on the economic development of the district-city in Sumatra, Indonesia. The theory of regional economic growth used Keynesian models and Concept Capital expenditure for the Public Utility Law according to Wagner. Previous empirical research, among others: (a) Susetyo et al. (2017), (b) Prasetyo (2013), (c) Yanizar (2012). Research methods include (a) the scope of public utilities is capital expenditure, the number of customers of electricity, water, telephone and the gross regional domestic product (GRDP). The unit of analysis is the district-city as much as 155 in Sumatra-Indonesia; (b) the data used is secondary data and source of data from the official publication; (c) the method is quantitative analysis and estimation method is multiple ordinary least square method of panel data. The result is simultaneously (F-test) showed that the results obtained are four variables observed were regional public utility capital expenditures, the number of electricity customers, the number of water customers, the number of telephone subscriber positive effect on the GRDP regencies-cities significantly. Partially (t-test), indicating that capital expenditure has positive influence local public utilities to GRDP regencies and cities significantly. The local public utility capital expenditures are a positive and significant influenced. Likewise, shows that the effect of the number of customer electricity, clean water, the phone toward the regional gross domestic product is positive and significant. Analyzing coefficient of determination (R2) is 62.02% means the results of the model estimates the variation can be explained by four variables and significantly. Keywords: Regional Economy, Capital Spending Public Utilities, Customers of Electricity, Clean Water and Telephone JEL Classifications: O10, H50, H54, H70